When to introduce an online channel, and offer money back guarantees and personalized pricing? - Chen, Bintong; Chen, Jing (European journal of operational research, 2017)
•A dual-channel in which the online channel faces a high customer returns.•We identify conditions a retail/an online channel, or a dual-channel structure should be chosen.•A simple three-step process to make decisions on channel selection, returns policy, and price.•Implementing PP makes the online channel more attractive and retailer more likely to adopt MBGs. Sales through an online channel are increasingly popular in the retailing industry. Customers, however, cannot touch or feel a product before they purchase online. This leads to much higher rates of customer returns in the online channel, which in turn leads to significant costs to retailers. In this paper, we develop a model of a dual-channel structure with online and brick-and-mortar channels, in order to determine when a retailer should introduce an online channel and how it should define returns policies for the two channels. We identify the conditions under which a retailer should choose a dual-channel structure, and show that the retailer should offer a Money-Back Guarantee (MBG) in a channel as long as the net salvage value of the returned product is positive in that channel. In addition, if uniform pricing is used in both channels, it is optimal for the retailer to simply set the prices for each channel as if the two channels were operated separately. Our analysis leads to a simple three-step process to help the retailer make a channel selection, choose a product returns policy, and decide on price. We also examine the implications of personalized pricing (PP) in the online channel for the retailer's channel selection and choice of returns policy. We show that PP makes the online channel more attractive and makes the retailer more likely to adopt MBGs. The impact of PP on pricing for both channels is also discussed.